PENGGUNAAN MODEL DISCOVERY LEARNING GUNA MENCIPTAKAN KEMANDIRIAN DAN KREATIVITAS PESERTA DIDIK - Muhammad Fikri Sunarto; Nur Amalia (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
In teaching and learning activities, the learning model is an important part of the learning tools that must be prepared by the teacher before teaching. The available learning models also vary, according to their respective functions. One of the learning models that is widely used is the Discovery Learning model. This learning model makes student more active, can think more critically, develop creativity, and also make student more independent. The Discovery Learning model makes student more involved in learning activities and teachers only as facilitators ini learning. That way, student can be more comfortable and stimulated ini learning by using this Discovery Learning model.